Association of Short-Term Heart Rate Variability With Breast Tumor Stage - Wu, Shuang; Chen, Man; Wang, Jingfeng; Shi, Bo; Zhou, Yufu (Frontiers in Physiology, 2021)
Cardiac autonomic modulation, assessed by heart rate variability (HRV), is associated with tumor pathogenesis and development as well as invasion and metastasis. This study aimed to examine this association in breast cancer patients. A total of 133 patients (average age 49.2 years) with breast cancer or benign breast tumors were divided into three groups: benign group, early-stage group, and advanced-stage group. Five-minute resting electrocardiogram was collected for the analysis of linear and nonlinear HRV parameters. Multiple logistic regression models were performed to test the independent contribution of HRV to breast tumor stage. The advanced-stage group had significantly reduced HRV compared to the benign and early-stage groups. In particular, for each 1-standard deviation (SD) increase in SD2, SD of normal-to-normal intervals, very-low frequency, total power, and low frequency, the odds of having advanced staging decreased by 69.3%, 64.3%, 58.3%, 53.3%, and 65.9%, respectively. These associations were independent of age, body mass index, mean heart rate, and respiratory rate. These findings suggest an association between HRV and breast tumor stage, and HRV parameters may help construct an effective early diagnostic and clinical prognostic model.